APPLICATION OF HYSTERESIS ENVELOPE MODEL TO STEEL BEAM-TO-COLUMN BOLTED JOINT (Collection of scientific works «Modern structures of metal and wood», 2022)
The paper demonstrates the applications of the hysteresis envelope model on the example of a double extended end plate beam-to-column bolted joint. The hysteresis envelope model represents  a  new  analytical  trilinear  model  that  can  describe  the  cyclic  behaviour  of  joints  in  a moment-resisting steel frame and is suitable for nonlinear static pushover analysis. The principle of determining the parameters of the hysteresis model is based on the monotonic curve of joint, which can  be  determined  by  applying  the  Component  method  using  commercial  software  for  the  joint design.  After  trilinear  idealisation  of  nonlinear   −  curve,  the  parameters  of  the  hysteresis envelope model  are then obtained by multiplying the parameters of the  monotonic model with a nonlinear  exponential  function.  Predicting  the  cyclic  behaviour  of  the  joint  using  the  hysteresis envelope model is satisfactory for further practical application.